2012
DOI: 10.1111/j.1751-2980.2012.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in various functional gastrointestinal disorders: Do differences exist?

Abstract: OBJECTIVE:To examine the differences in the prevalence and severity of anxiety and depression in patients with functional dyspepsia (FD), nonerosive reflux disease (NERD), irritable bowel syndrome (IBS) and healthy controls. METHODS:Consecutive patients undergoing an index endoscopic examination for various symptoms were interviewed. All the three functional gastrointestinal disorders (FGIDs) were diagnosed according to the Rome III criteria. Anxiety and depression were diagnosed using a locally validated vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 39 publications
4
52
0
3
Order By: Relevance
“…Subjects reporting anxiety without depression had a 3.2-fold increased risk of reflux, subjects with depression without anxiety had a 1.7-fold increased risk and subjects with both anxiety and depression had a 2.8-fold increased risk, compared to subjects without anxiety or depression, suggesting anxiety and depression are strongly associated with reflux symptoms [9,10] (Figure 4). Furthermore, clinical trials have demonstrated that, adding Tricyclic antidepressant to a PPI was more effective than a doubledose of PPI in patients with FCP refractory to a conventional dose of PPI.…”
Section: Gerd and Psychological Comorbiditymentioning
confidence: 99%
“…Subjects reporting anxiety without depression had a 3.2-fold increased risk of reflux, subjects with depression without anxiety had a 1.7-fold increased risk and subjects with both anxiety and depression had a 2.8-fold increased risk, compared to subjects without anxiety or depression, suggesting anxiety and depression are strongly associated with reflux symptoms [9,10] (Figure 4). Furthermore, clinical trials have demonstrated that, adding Tricyclic antidepressant to a PPI was more effective than a doubledose of PPI in patients with FCP refractory to a conventional dose of PPI.…”
Section: Gerd and Psychological Comorbiditymentioning
confidence: 99%
“…78 Psychological stress increased the perception of heartburn and aggravated GERD symptoms. 79,80 Fass et al 81 have shown that acute stress can enhance the sensitivity to intraesophageal acid perception in both reflux esophagitis or NERD patients.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%